2017
DOI: 10.1016/j.exphem.2017.09.001
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-22 controls interferon alpha production and erythroid maturation in response to infectious stress in mice

Abstract: MicroRNA-22 (miR-22) is a highly conserved microRNA that can regulate cell proliferation, oncogenesis, and cell maturation, especially during stress. In hematopoietic stem cells (HSCs) miR-22 has been reported to be involved in the regulation of key self-renewal factors including Tet2. Recent work demonstrates that miR-22 also participates in regulation of the interferon response, and expression profiling studies suggest that it is variably expressed at different stages in erythroid differentiation. We thus hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 37 publications
(49 reference statements)
1
12
1
Order By: Relevance
“…fIncreasing reports demonstrate miRNAs exert roles via binding to 3ʹ-UTR of target mRNAs [15]. Thus, we looked for the potential target of miR-1228 by using TargetScan and miRanda.…”
Section: Mir-1228 Targeted Tcf21 In Lung Cancermentioning
confidence: 99%
“…fIncreasing reports demonstrate miRNAs exert roles via binding to 3ʹ-UTR of target mRNAs [15]. Thus, we looked for the potential target of miR-1228 by using TargetScan and miRanda.…”
Section: Mir-1228 Targeted Tcf21 In Lung Cancermentioning
confidence: 99%
“…47 Lastly, coupled with signatures indicating posttranslational remodeling of the erythroid proteome, we also identified factors involved in the posttransriptional control of erythropoiesis. Transcription of MIR22HG, for example, a gene coding for a microRNA controlling erythroid maturation in mice (MIR22), 48 was upregulated in the GFP 1 fraction. Similarly, RBM38 and CPEB4 were found upregulated in the GFP 1 vs GFP 2 fraction (Figure 3).…”
Section: Gfp 1 B-globin-expressing Ipsc-derived Erythroid Cells Displmentioning
confidence: 99%
“…MicroRNA‐22 (miR‐22) is located on the 17p13 chromosome and happens to be evolutionarily conserved. This highly conserved microRNA plays a significant role in oncogenesis, cell maturation, as well as cell proliferation, especially during stress. Previous research has demonstrated that MiR‐22 functions as a tumor suppressor in different malignancies, such as prostatic, breast, and gastric cancers.…”
Section: Introductionmentioning
confidence: 99%